Struktura i idea kołchozu a wspólnoty lokalne tradycyjnych społeczeństw Azji Środkowej - Książek, Joanna (Zeszyty Wiejskie, 2012)
Diverse kinds and levels of the ethno-cultural identity of a tribal or terriorial origin is a distinctive feature of the traditional societies of the Central Asia. During the Soviet period one of the factors interfering with the comlpex constelation of this identity layers was collectivisation on the rural areas. The point was to destroy the traditional society in favour of the homo sovieticus. How it comes, that the kolkhos became a part of the framework of the traditional tribal-based networks? In what way did the Soviet practices leave their stamp on the solidarity groups present on that area? Does something like kolkhosian identity really exist? Is it still a part of the present-day identity of the citizens from the independent states of Central Asia? All this questions I would like to answer in this article.